A Changing Climate for Anthropological and Archaeological Research? Improving the Climate‐Change Models. Issue 3 (17th July 2014) - Roscoe, Paul
ABSTRACT Climate change is the latest in a dismaying series of challenges that industrialism and modernity have gifted to humanity. To date, anthropological and archaeological responses have focused largely on the culturally particular—that is, on the interactions of climate, environment, cultural schema, and social systems in specific locales and eras. In this article, I urge a complementary response that capitalizes on archaeology and anthropology's holistic and universalistic investigative aspirations and expertise. For two decades, the Intergovernmental Panel on Climate Change (IPCC) has overseen major efforts to model human social dynamics and their implications for future climate change. These models are technically sophisticated but economically reductionist and substantively crude. Here, I review these efforts and provide three examples of how established and future archaeological and anthropological research could improve them. Recent changes to the IPCC's modeling regime make this an opportune moment for such a project.